Geochemistry, petrography and tectonic significance of the ophiolitic rocks, felsic intrusions and Eocene volcanic rocks of an imbrication zone (Helete area, Southeast Turkey) - Yildirim, Esra (Pergamon-Elsevier Science Ltd, 2015)
The study area is situated in the imbrication zone (northwest of Athyaman-Golbasi Helete-Savran) of the Southeast Anatolian orogen, part of the Mediterranean-Himalayan orogenic belt. This area is characterized by NEE/SWVV-trending, northward-dipping imbricated thrust slices located low in the nappe zone that was finally emplaced onto the Arabian platform during the Mid-Miocene. From top to bottom the main units in the study area are: (1) the Malatya Metamorphics- (2) the Harami Formation- (3) the Goksun Ophiolite-Esence Granitoid- (4) the Helete volcanics and (5) the Savran-Alacik Formation, Hompur-Lice Formation and Midyat Formation. This study contains the Upper Cretaceous-Eocene tectono-magmatic succession (ophiolitic rocks and related felsic intrusions and volcanic rocks), which are located in the Helete area. The unmetamorphosed ophiolitic rocks display an irregular ophiolitic sequence. These rocks are represented by tectonites, cumulated gabbros, isotropic gabbros and sheeted dyke complex and were intruded locally by felsic intrusions (granite, granodiorite, tonalite, dacite, and aplite). These ophiolites locally contain tectonically disrupted thin amphibolitic rocks. The mineral chemistry and geochemical features of these ophiolites indicate that these rocks exhibit sub-alkaline characteristics, and they are similar to those of island arc tholeiites formed in a supra-subduction zone. These ophiolitic rocks, located in the imbrication zone, are interpreted as being the equivalent of the Goksun Ophiolites. The felsic intrusions, which cut these ophiolitic rocks, correspond to the calc-alkaline Esence Granitoids which formed in an arc setting. Based on the 40Ar/39Ar dating method, a plateau age of 80.92 +/- 0.29 Ma was obtained from a granite sample that cuts the gabbroic rocks. The Helete volcanics, which have a tectonic relationship with the Goksun Ophiolite and the Esence Granitoid, are represented by andesite-basalt (locally pillow lavas), and are overlain by nummulitic carbonate sediments. Geochemical data indicated that, the Helete volcanics evolved from a tholeiitic parental magma and formed in a subduction-related setting. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Helete; Ophiolite; Felsic intrusion; Imbrication zone; Island-arc; SE Anatolia